Leafhopper males compensate for unclear directional cues in vibration-mediated mate localization - Jernej Polajnar; Anka Kuhelj; Rok Janža; Nada Žnidaršič; Tatjana Simčič; Meta Virant-Doberlet (Scientific Reports, 2023)
Abstract Ambient noise and transmission properties of the substrate pose challenges in vibrational signal-mediated mating behavior of arthropods, because vibrational signal production is energetically demanding. We explored implications of these challenges in the leafhopper Aphrodes makarovi (Insecta: Hemiptera: Cicadellidae) by exposing males to various kinds of vibrational noise on a natural substrate and challenging them to find the source of the female playback. Contrary to expectations, males exposed to noise were at least as efficient as control males on account of similar searching success with less signaling effort, while playing back male–female duets allowed the males to switch to satellite behavior and locate the target without signaling, as expected. We found altered mitochondrial structure in males with high signaling effort that likely indicate early damaging processes at the cellular level in tymbal muscle, but no relation between biochemical markers of oxidative stress and signaling effort. Analysis of signal transmission revealed ambiguous amplitude gradients, which might explain relatively low searching success, but it also indicates the existence of behavioral adaptations to complex vibrational environments. We conclude that the observed searching tactic, emphasizing speed rather than thorough evaluation of directional cues, may compensate for unclear stimuli when the target is near.